منهجية البحث وإشكالية التأصيل للاقتصاد الكلي الاسلامي: Research Methodology and the Problem of Rooting of Islamic Macroeconomics - محمد فرحي (Journal of North African Economies, 2025)
This research paper starts from noting the absence of an agreed definition of Islamic economics and the weakness of studies dealing with macroeconomics from an Islamic perspective. holistic; The paper does not assert that what it contains is the Islamic perspective, but rather suggests an entry that may be a field of enrichment and discussion for in-depth research.